Thoracic growth deficiency in childhood cancer survivors may cause overestimation of lung disease. Issue 10 (3rd July 2019) - Dean, Terry; McDonough, Joseph M.; Josephson, Maureen; Ginsberg, Jill P.; Carlson, Claire A.; Fiorino, Elizabeth K.; Goldfarb, Samuel B.
Abstract: Introduction: Survivors of childhood cancers undergo routine pulmonary function testing as they are at an increased lifetime risk for significant lung disease. However, this population also demonstrates growth abnormalities that could influence the interpretation of these tests, as reference equations are based on standing height. We aim to determine the impact of the relative thoracic growth deficiency in childhood cancer survivors on the interpretation of pulmonary function testing. Methods: Standing height and upper segment length (USL) in childhood cancer survivors undergoing pulmonary function testing at a single academic center were compared to age‐matched historical standards. Additionally, pulmonary function tests were compared to reference values generated from standing height and doubled USL. Results: Data were obtained from 107 cancer survivors. While the subjects demonstrated an overall 6.8% lower standing height vs historical standards, they also demonstrated relative thoracic growth abnormality with a further 9.9% decrement in the ratio USL to standing height. The use of doubled upper segment length as a surrogate measure for standing height in pulmonary function reference equations decreased the number of patients with restrictive lung disease as indicated by spirometry. Conclusions: Childhood cancer survivors have disproportionately worse thoracic growth deficiency vs appendicular growth deficiency. As a result, their USL is disproportionately short for their standing height, which is most commonly used in pulmonary function testing reference equations. This leads to an increased likelihood in these patients meeting pulmonary function test criteria for restrictive lung disease.